2019
DOI: 10.22161/ijeab.45.40
|View full text |Cite
|
Sign up to set email alerts
|

Effect of Supplementation of Rumen-Protected Amino Acids to Barki Sheep on Some Blood Parameters

Abstract: The objective of this study was to evaluate the effects of supplementing a traditional diet with rumenprotected (RP) either methionine (MET) or lysine (LYS) or their combination, on some physiological responses of ewes. Twenty-four adult Barki ewes were used were divided into four groups (6 ewes for each). The first group (Control) was fed only the control diet. The second group (LYS) fed the control diet and rumen-protected LYS (6g Lysi pearl /kg concentrate i.e. 3g /animal/day). The third group (MET) was fe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2021
2021
2021
2021

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(3 citation statements)
references
References 12 publications
(13 reference statements)
0
3
0
Order By: Relevance
“…Glucose and free fatty acids concentrations are good indicators of the energetic status. The supply of methionine enhanced the capacity of the liver in exporting triacylglycerols in the form of very-low-density lipoprotein and helping improve the negative effect of fatty acid collecting in the liver (Younis and Abd-Elazem 2019). However, Li et al (2015) did not find any such effects in blood cholesterol and triglycerides in lambs receiving an estimated dose of 37 to 116 mg/kg.…”
Section: Glucose Cholesterol and Triglyceridesmentioning
confidence: 88%
See 2 more Smart Citations
“…Glucose and free fatty acids concentrations are good indicators of the energetic status. The supply of methionine enhanced the capacity of the liver in exporting triacylglycerols in the form of very-low-density lipoprotein and helping improve the negative effect of fatty acid collecting in the liver (Younis and Abd-Elazem 2019). However, Li et al (2015) did not find any such effects in blood cholesterol and triglycerides in lambs receiving an estimated dose of 37 to 116 mg/kg.…”
Section: Glucose Cholesterol and Triglyceridesmentioning
confidence: 88%
“…The obtained values of plasma content of methionine in this study agree with Youssef (2017), who measured plasma content of methionine in Barki sheep and the maximum value was (0.40%±0.02). Also, Younis and Abd-Elazem (2019) found that adding protected amino acids lysine or/and methionine caused a significant increase in lysine, glutamic, and arginine concentrations, while it caused a significant decrease in proline and ammonia concentrations. Ramadan et al, (2017) found that concentrations of arginine, glutamic, and lysine in Barki sheep increased significantly when protected amino acids methionine and lysine were supplemented, for diets ewes but ammonia and proline concentrations decreased significantly.…”
Section: Glucose Cholesterol and Triglyceridesmentioning
confidence: 95%
See 1 more Smart Citation